2015
DOI: 10.1063/1.4915305
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing shallow color centers in diamond created by nitrogen delta-doping using SF6 plasma treatment

Abstract: Influence of a static magnetic field on the photoluminescence of an ensemble of nitrogen-vacancy color centers in a diamond single-crystal Appl. Phys. Lett. 95, 133101 (2009);

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…Existing studies include reports of CVD growth that demonstrated a narrow distribution in the confinement of NV centers in the vicinity of a surface 11 and their atomic alignment on (100), (110), (113), and (111) substrates for the formation of thick diamond films 14,15,16,17,18,19,20 . Nearly all previous studies have focused on either low density NV centers (<10 13 cm -3 3 ) in the vicinity of a surface with no alignment 21,22,23 or the formation of NV ensembles with alignment in bulk.In this paper, the formation of a perfectly aligned high-density shallow NV center film for surfacesensitive detection of nuclear spin has been demonstrated. Results obtained from SIMS measurement combined with an effective depth obtained from nanoscale NMR measurement confirms presence of shallow NV center approximately 9-10.7 nm from surface with error of less than ±0.8 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies include reports of CVD growth that demonstrated a narrow distribution in the confinement of NV centers in the vicinity of a surface 11 and their atomic alignment on (100), (110), (113), and (111) substrates for the formation of thick diamond films 14,15,16,17,18,19,20 . Nearly all previous studies have focused on either low density NV centers (<10 13 cm -3 3 ) in the vicinity of a surface with no alignment 21,22,23 or the formation of NV ensembles with alignment in bulk.In this paper, the formation of a perfectly aligned high-density shallow NV center film for surfacesensitive detection of nuclear spin has been demonstrated. Results obtained from SIMS measurement combined with an effective depth obtained from nanoscale NMR measurement confirms presence of shallow NV center approximately 9-10.7 nm from surface with error of less than ±0.8 nm.…”
mentioning
confidence: 99%
“…Existing studies include reports of CVD growth that demonstrated a narrow distribution in the confinement of NV centers in the vicinity of a surface 11 and their atomic alignment on (100), (110), (113), and (111) substrates for the formation of thick diamond films 14,15,16,17,18,19,20 . Nearly all previous studies have focused on either low density NV centers (<10 13 cm -3 3 ) in the vicinity of a surface with no alignment 21,22,23 or the formation of NV ensembles with alignment in bulk.…”
mentioning
confidence: 99%
“…-An N-doped, several nm-thick layer, the δ-doped layer [47,48], is created in situ by the controlled introduction of N 2 gas during slow, plasma-enhanced CVD growth of single-crystal diamond (growth rate ≈ 0.1 nm/min; Figure 2a). Changing the N 2 flow tunes the resulting N densities.…”
Section: Creation Methods and Creation Yieldmentioning
confidence: 99%
“…Here, we describe a preparative and high‐yielding method for one‐step fluorination of NDs that can be performed on a benchtop using modest synthetic equipment. Our interest in fluorination of NDs arose from recent studies showing that fluorination of the diamond surface can be used to stabilize negatively charged nitrogen‐vacancy (NV − ) centers located close to the surface. These atomic defects in the diamond lattice have been thoroughly studied in the past two decades due to their unique applications as single photon emitters, ultrasensitive magnetic, and electric field sensors, chemical probes, and qubits .…”
Section: Introductionmentioning
confidence: 99%